2017
DOI: 10.7554/elife.28751
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral mGluR5 availability contributes to elevated sleep need and behavioral adjustment after sleep deprivation

Abstract: Increased sleep time and intensity quantified as low-frequency brain electrical activity after sleep loss demonstrate that sleep need is homeostatically regulated, yet the underlying molecular mechanisms remain elusive. We here demonstrate that metabotropic glutamate receptors of subtype 5 (mGluR5) contribute to the molecular machinery governing sleep-wake homeostasis. Using positron emission tomography, magnetic resonance spectroscopy, and electroencephalography in humans, we find that increased mGluR5 availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 67 publications
(90 reference statements)
9
51
3
Order By: Relevance
“…Based on immunocytochemistry, it was suggested that most rat GABAergic preoptic neurons that project to the histamine neurons in the posterior hypothalamus co-released galanin (66); indeed, galanin directly reduces the firing rate of histamine neurons (67). Activating optogenetically GABAergic (non-galanin) 13 terminals from the PO hypothalamus in the area where the histamine neurons are located induces NREM sleep (64). On the other hand, optogenetic activation of PO galanin neuron soma produced wakefulness (64); this result could be caused by other galanin neuron subtypes (68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on immunocytochemistry, it was suggested that most rat GABAergic preoptic neurons that project to the histamine neurons in the posterior hypothalamus co-released galanin (66); indeed, galanin directly reduces the firing rate of histamine neurons (67). Activating optogenetically GABAergic (non-galanin) 13 terminals from the PO hypothalamus in the area where the histamine neurons are located induces NREM sleep (64). On the other hand, optogenetic activation of PO galanin neuron soma produced wakefulness (64); this result could be caused by other galanin neuron subtypes (68).…”
Section: Discussionmentioning
confidence: 99%
“…Widely expressed genes (e.g. Sik3, Adora1, clock, mGluR5, per3, reverba) have been found to modulate sleep homeostasis (9,(11)(12)(13)(14)(15)(16)(17). Astrocytes and skeletal muscle release messengers which can modulate the process (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…We next assessed whether humans showed a similar heterogeneity in the response of δ power to SD. A total of 110 healthy human subjects from four published datasets who underwent wholenight SD amounting a sustained waking period of 40h (Bodenmann et al, 2009, Holst et al, 2017, Valomon et al, 2018, Weigend et al, 2019, were included in the analysis. Here we show only the aggregate results, but similar results were obtained in each study separately.…”
Section: Distinct δ Sub-bands Are Present In the Human Brain Followinmentioning
confidence: 99%
“…All subjects signed informed consent and were compensated financially for participating. For more details see previous publications (Bodenmann et al, 2009, Holst et al, 2017, Valomon et al, 2018, Weigend et al, 2019. Some subjects were removed across 5 studies for signal artifacts, which made time-course analysis of spectral bands difficult.…”
Section: Study Participantsmentioning
confidence: 99%
“…In humans, mGluR5 show high expression in brain regions regulating sleep (Hefti et al, 2013) and their functional availability was increased after prolonged wakefulness (Hefti et al, 2013). Furthermore, increased mGluR5 availability correlated with behavioral and neurophysiological markers of elevated sleep need, including self-rated sleepiness, unintended sleep during prolonged wakefulness, as well as SWA and slow (< 1 Hz) oscillatory activity in the NREM sleep EEG (Hefti et al, 2013;Holst et al, 2017).…”
Section: Introductionmentioning
confidence: 99%